Authenticity, experience, and loyalty in the festival context: Evidence from the San Fermin festival, Spain. Issue 15 (18th November 2017) - Girish, V.G.; Chen, Ching-Fu
Abstract : This study empirically investigates the relationships among authenticity, experience – measured by emotions (i.e. pleasure and arousal) along with satisfaction, and loyalty in the festival context. Structural equation modelling is employed to examine a sample of 211 visitors attending the San Fermin festival in Spain. Results show that authenticity positively affects experience, while on the other hand, only arousal has positive effects on satisfaction and festival loyalty. Satisfaction is positively associated with festival loyalty.